Memoria e historia : una aproximación internacional desde el ámbito jurídico - Manuel Sánchez-Moreno (Amnis)
This paper refers to two traditionally separate disciplines: Humanities and Legal Sciences. Both disciplines have been understood from a positivist point of view that has dissected them two different fields. It is not possible to focus only on legal texts to address certain problems such as democratic memory. To this end, an interdisciplinary methodology is essential, using the Humanities and History for legal practice, and considering the humanity of the victims in the interpretation of the Law. For this purpose, the contributions of History to jurisprudence will be analysed in two case studies: the last Argentine dictatorship and the Francoism in Spain.